A group learning curve model with and without worker turnover. (15th July 2014) - H. Glock, Christoph; Y. Jaber, Mohamad
Abstract : Purpose: – The purpose of the paper is to develop a mathematical model that describes group learning processes with and without worker turnover. Design/methodology/approach: – Based on an extensive literature review, fundamental characteristics of group learning processes are first identified and then incorporated into a group learning curve (GLC). The developed GLC is then validated by fitting to empirical data. Findings: – The results show that the behaviour of the developed model is in conformance with the characteristics identified in the literature. A comparison with two other learning curves that have frequently been discussed in the literature shows that the GLC developed in this paper is a good mathematical representation of group learning processes. Practical implications: – The model developed in this paper enables practitioners to predict performance improvement in groups. Originality/value: – The paper is one of the first to propose a mathematical formulation of a GLC.